2020
DOI: 10.3390/biology9120473
|View full text |Cite
|
Sign up to set email alerts
|

Incretin Hormones and Type 2 Diabetes—Mechanistic Insights and Therapeutic Approaches

Abstract: Glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) are secreted from the gut upon nutrient stimulation and regulate postprandial metabolism. These hormones are known as classical incretin hormones and are responsible for a major part of postprandial insulin release. The incretin effect is severely reduced in patients with type 2 diabetes, but it was discovered that administration of GLP-1 agonists was capable of normalizing glucose control in these patients. Over the last de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 159 publications
0
56
0
2
Order By: Relevance
“…Glucagon-like peptide-1 (GLP-1), an incretin hormone mainly secreted from intestinal L cells, has gained attention as a key player in the pathogenesis of metabolic and inflammatory diseases due to its function in modulating ER stress and promoting anti-inflammatory signaling [48]. The insulinotropic and glucose-lowering effects of GLP-1 has long been shown to be impaired in obesity and T2D [49], and GLP-2, another co-secreted L-cell peptide hormone that improves gut epithelial proliferation and mucosal integrity, has also been found to be reduced in obese mice and humans [50,51]. Secretion of GLP-1 and GLP-2 also has been found to be impaired by chronic exposure to TNFα [52,53] and, inversely, it was reported that GLP-1 or GLP-1 receptor (GLP-1R) agonists reduce the levels of pro-inflammatory cytokines [54] and the activation of GLP-1R signaling modulates intestinal immune responses and mucosal inflammation [55].…”
Section: Metabolic-endocrine Link Between Metabolic Disorders and Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucagon-like peptide-1 (GLP-1), an incretin hormone mainly secreted from intestinal L cells, has gained attention as a key player in the pathogenesis of metabolic and inflammatory diseases due to its function in modulating ER stress and promoting anti-inflammatory signaling [48]. The insulinotropic and glucose-lowering effects of GLP-1 has long been shown to be impaired in obesity and T2D [49], and GLP-2, another co-secreted L-cell peptide hormone that improves gut epithelial proliferation and mucosal integrity, has also been found to be reduced in obese mice and humans [50,51]. Secretion of GLP-1 and GLP-2 also has been found to be impaired by chronic exposure to TNFα [52,53] and, inversely, it was reported that GLP-1 or GLP-1 receptor (GLP-1R) agonists reduce the levels of pro-inflammatory cytokines [54] and the activation of GLP-1R signaling modulates intestinal immune responses and mucosal inflammation [55].…”
Section: Metabolic-endocrine Link Between Metabolic Disorders and Ibdmentioning
confidence: 99%
“…Adipose tissue dysfunction ↓adiponectin, ↓omentin-1, ↑leptin, ↑resistin, ↑visfatin, and ↑chemerin in obesity and/or T2D * [40][41][42] ↓adiponectin, ↓omentin-1, ↓or↑leptin in IBD * [45][46][47], ↑resistin, ↑visfatin, and ↑chemerin in IBD * [44][45][46][47] Enteroendocrine cell dysfunction ↓GLP-1 [49], ↓GLP-2 [50,51], and ↑DPP-4 in obesity and T2D [56] ↑GLP-1 and ↑GLP-2 in IBD [58] ↓DPP-4 in IBD [60] Intestinal barrier dysfunction ↓ZO-1, occludin in DIO and ob/ob mice * [50,65] ↓ZO-1, occludin, claudin-1 in rodent DIO models * [66] ↓claudin-1, -3, -4, -7, -15, and ↑claudin-2 (the leaky claudin) in rodent DIO models * [67] ↓occludin, tricellulin in obese patients with T2D * [68] ↓fecal zonulin in obese patients * [69] ↓ZO-1, occludin, but no change of claudin-1 in NAFLD patients * [70] ↓claudin-4 in both CD and UC * [71] ↓claudin-5, -8 in CD * [72] ↑claudin-1 in active forms of both CD and UC * [73][74][75], but no change in inactive forms [74] ↑claudin-2 in both CD and UC * [71,72,74], ↓occludin in CD* [72,75,76], no change [74]↓ZO-1 in colonic epithelial cell culture [76] and DSS-induced colitis mice * [75] Polymorphisms of genes encoding tight junction-associated proteins in IBD patients [77,78] ↑apoptosis [79][80]…”
Section: Metabolic Disorders Ibdmentioning
confidence: 99%
“…The 2 types of incretin-based therapies are glucagon-like peptide (GLP)-1 receptor agonists, and inhibitors of the incretin-degrading enzyme dipeptidyl peptidase-4 (DPP-4). 3 …”
Section: Introductionmentioning
confidence: 99%
“…In fact, due to its effect on insulin secretion, the incretin effect represents an important mechanism for the regulation of plasma insulin concentration. However, GLP-1 and GIP receptors are also expressed in other tissues, such as adipose, heart, kidney, bone, brain [3,4], and possibly liver [5] tissue, though the related functions remain mainly unknown [6].…”
Section: Introductionmentioning
confidence: 99%